Innovative Business Models for Expanding Fiber-Optic Networks and Closing the Access Gaps - World Bank Group (World Bank, Washington, DC, 2018)
The increasing importance of the Internet, not only for tasks related to information search, storage, and sharing, but also for connecting people and business, domestic and international trade, education, entertainment and social interactions, has led governments around the world to include Internet connectivity in their priority policy agendas and infrastructure plans. Today, access to the Internet is no longer a luxury, but is increasingly considered an essential service, as important as building transportation and utility networks. However, more than four billion people, overwhelmingly in developing countries, still lack Internet access. For the past decade, policy makers have sought ways to best create an enabling environment to direct national resources and engage the private sector to effectively expand access to the Internet. In doing so, policy makers and regulators face a unique combination of priorities, resources, market structures, and geographies that will affect their national plans. Experience shows that no one-size-fits-all approach exists, but past and current experience can be analyzed for common factors contributing to success or failure to support similar endeavors in the future. This report reviews and provides guidance on innovative business models and approaches to the deployment of high-speed broadband networks and highlights global trends related to terrestrial spectrum resources that can be leveraged to meet expected future demand and close existing Internet access gaps. It is intended to serve as a reference tool to help policy makers and regulators assess alternatives for infrastructure deployment and adopt decisions tailored to their country’s circumstances and needs.